Capillary problem and mean curvature flow of killing graphs. - WANDERLEY, Gabriela Albuquerque. (2013)
We study two typ es of Neumann problem related to Capillary problem and to the evolution of graphs under mean curvature flow in Riemannian manifolds endowed with a Killing vector field. In particular, we prove the existence of Killing graphs with prescrib ed mean curvature and prescrib ed b oundary conditions.